An Insight into Menstrual Disorders and Female Reproductive Health: A Cross Sectional Study of Females in the Darjeeling Region - Chhetri, Udrishya; Gurung, Yuvraj (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Background: Menstruation is a critical phenomenon in women’s life. However, variability in menstrual cycle characteristics and menstrual disorders are common. The purpose of this study was to determine the menstrual characteristics of females, its association with disorders and complications and overall female health. Methods: The study was conducted to evaluate the menstruation disorders and common female complications and its severity in females and its effect on their regular activities. This is a cross-sectional study; conducted on 303 females in Darjeeling Himalayan region, structured questionnaires were used to gather the socio- demographic data, age at menarche, regularity in menses and dysfunctions. Data was analyzed using spss-16 and excel-2019. Results: In the study mean age of menarche was found to be 12.94±1.69 year and menopause ages 45.4±6.45 years. Menarche and menopause age shows positive relation. The majority 59.1% (179) experienced dysmenorrhea, 33% menorrhagia, 22.1%(67) hypo menorrhagia followed byoligomerorrhea is 21.1% (64 females) and Polymenorrhea is 13.2% (40).(Fig: 2).Both early and late menarche was seen to be related to menstrual dysfunction among women. Menstrual disturbances were more prevalent among women who experienced menarche at a younger age and those with dieting habits. Consumption of alcohol, tobacco and junk food had negative impact leading to various menstrual disorders. Conclusion: Menstrual problems among females are common and notions about female health are still in base. The study being the pilot project in this region seeks attention for help of females all around, for the education and educare of female child starting from education about periods to usage of right sanitary products, education about menstruation and its complications, importance of seeking help.